Frontiers and Progress in Multiphase Flow I - Cheng, Lixin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume presents state-of-the-art of reviews in the field of multiphase flow. In focusses on nonlinear aspects of multiphase flow networks as well as visualization experiments. The first chapter presents nonlinear aspects or deterministic chaos issues in the systems of multi-phase reactors.  The second chapter reviews two-phase flow dynamics in combination with complex network theory. The third chapter discusses evaporation mechanism in the wick of copper heat pipes. The last chapter investigates numerically the flow dynamics and heat and mass transfer in the laminar and turbulent boundary layer on the flat vertical plate.
Selected Aspects of Thermal-Hydraulics Modelling in Two-Phase Flows with Phase Change in Mini-channels -- Flow Characteristics and Void Fraction Prediction in Large Diameter Pipes -- Physical Water Treatment Using Oscillating Electric Fields to Mitigate Scaling in Heat Exchangers -- Flow Patterns, Void Fraction and Pressure Drop in Gas-Liquid Two Phase Flow at Different Pipe Orientation.
Keywords: Fluid mechanics; Fluids; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Engineering Thermodynamics, Heat and Mass Transfer